The challenge of clinical management of Cushing’s disease: case report - Melo, Isabela Moreira (2022)
Cushing's disease is caused by the corticotrophic pituitary adenoma which increases the level of cortisol and consequently blood glucose levels and the deposition of fat in tissues and organs. This study proposes to report the case of a patient with this rare pathology in order to understand the syndrome that hypercortisolism/adenoma results in and discuss the clinical challenge. This is a case study whose data were obtained by evaluating the patient's medical records, analyzing the diagnostic tests performed and reviewing the literature. The 21-year-old patient complained of difficult-to-control obesity. Physical examination, laboratory and imaging tests were performed, which led to the diagnostic hypothesis of pituitary adenoma. After the surgical removal procedure, the material was sent to the anatomopathological examination for biopsy, which confirmed the diagnosis of corticotrophic pituitary adenoma. It is necessary to pay attention to the clinical abnormalities caused by excess cortisol related to the diagnosis, considering the need for a multidisciplinary treatment.